Artificial breeding of the hawksbill turtle, Eretmochelys imbricata, in a captive facility in the Republic of Korea - Eunvit Cho; Dae-Yeon Moon; Il-Hun Kim; Donjin Han; Ki-Young Lee; Il-Kook Park (Nature Conservation)
Captive breeding has been conducted across various regions to restore globally endangered sea turtle populations. However, understanding how turtles adapt to artificial breeding environments that differ considerably from their natural habitats remains underexplored. This study focused on the artificial breeding of two male and two female hawksbill turtles, Eretmochelys imbricata, in a controlled facility in the Republic of Korea, isolated from the outdoor environment and located far north of their natural nesting grounds. The main objectives were to document the entire breeding process while identifying limitations in the breeding methods and suggesting improvements. During the study period, the hawksbill turtles laid 864 eggs across 10 clutches, resulting in 83 hatchlings. The mean fertilization rate was 33%, whereas hatching success rates were 10% and 32% for the number of total laid eggs and fertile eggs, respectively. A female turtle laid eggs two-and-a-half years after post-mating, demonstrating that hawksbill turtles can utilize long-term sperm storage for laying eggs in subsequent breeding seasons without additional mating. Enhancing captive breeding methods is crucial for improving the efficiency of sea turtle population recovery and expanding our understanding of their ecological characteristics.